Investment Flows and Country Development in Emerging Markets: Analysing the Impact of Foreign Investment on Economic Growth - BABAYEV, Farid; GONCHARENKO, Iryna; MAZUR, Hennadii; ABDULLAEV, Ulmas; CHERNYAHA, Lyudmyla (Theoretical and Practical Research in Economic Fields; Vol 15 No 4 (2024): TPREF Volume XV, Issue 4(32), Winter 2024, 2024)
The purpose of the article is to study the impact of investment flows on the economic development of Ukraine, Azerbaijan, and Uzbekistan, considering foreign investment, as well as to assess their contribution to the formation of sustainable economic growth. The methodology is represented by such methods of scientific knowledge as economic analysis, as well as SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The results of the study showed that foreign investment has a positive impact on the economic growth of developing countries, contributing to an increase in gross domestic product, reducing unemployment and stimulating technological progress. In addition, investment flows influence structural changes in the economy, facilitating the transition to more innovative and competitive arrangements. Additionally, successful attraction of foreign investment can improve the infrastructure and environmental situation in countries, which also favours their economic development. At the same time, the results of the study highlight the importance of creating a favourable investment climate to attract foreign investment and ensure sustainable economic growth, both now and in the future. However, it is important to understand the possible negative aspects of the impact of investment on the economy, including the issue of increased risks in the formation of dependence on foreign subsidies. The findings highlight the importance of seeking and attracting foreign investment to improve the economic performance of emerging market economies, as well as to stimulate sustainable economic growth and promote the integration of these economies into the global economic system, while minimizing negative impacts.